IMPLEMENTASI KEBIJAKAN PROGRAM PENGEMBANGAN KOTA LAYAK ANAK (KLA) DI KOTA BANDA ACEH TAHUN 2021 - Chicka Ayu Wulandari; Muliawati Muliawati; Novita sari (Journal of Political Sphere, 2022)
Child Friendly City (KLA) is a government program that refers to the protection of children and the fulfillment of children's rights. In 2021, Banda Aceh City received the KLA award at the Intermediate level and in the same year, cases of violence against children in Banda Aceh City were the highest cases compared to other districts in Aceh Province. So this is a question mark regarding the implementation of KLA in Banda Aceh City. This study aims to analyze the implementation of Child Friendly City (KLA) program development policies in Banda Aceh in 2021 and identify supporting and inhibiting factors for developing Child Friendly City (KLA) policies in Banda Aceh in 2021. The theory used is the theory of public policy implementation from Rippley and Franklin, namely the perspective of the compliance of the implementing apparatus and the smooth running of the routine. The method used is descriptive qualitative. The results of this study indicate that DP3AP2KB implementers understand their duties as the secretariat for the implementation of KLA in Banda Aceh City. Implementation of KLA program policies that have not gone well. This happens because the many actors involved do not have sufficient capacity in implementing KLA and the cooperation between actors in implementing KLA has not been maximized. The implementation of the KLA development program in Banda Aceh City only refers to the fulfillment of children's rights in terms of infrastructure facilities and protection of children's rights in the form of complaint services at the UPTD PPA and the Banda Aceh City Social Service. The supporting factor for KLA in Banda Aceh City is the support from the legislature and also the location of Banda Aceh as the capital, so that there is a lot of provincial infrastructure that can be used by the people of Banda Aceh City and also easy accessibility. While the inhibiting factors in the implementation of KLA in Banda Aceh City are the lack of human resources and the unfulfillment of standards as implementing KLA services, the difficulty of finding a pattern of cooperation between actors implementing KLA and also low community participation